Asynchrony of Apical Polarization, Luminogenesis, and Functional Differentiation in the Developing Thyroid Gland - Johansson, Ellen; Liang, Shawn; Moccia, Carmen; Carlsson, Therese; Andersson, Daniel; Fagman, Henrik; Nilsson, Mikael (Frontiers in Endocrinology, 2021)
Follicular thyroid tissue originates from progenitors derived from a midline endodermal primordium. Current understanding infers that folliculogenesis designates the latest morphogenetic event taking place after the final anatomical shape and position of the embryonic thyroid gland is established. However, this concept does not consider the fact that the thyroid isthmus develops chronologically before the lobes and also contains all progenitors required for lobulation. To elucidate whether cells committed to a thyroid fate might be triggered to differentiate asynchronously related to maturation and developmental stage, mouse embryonic thyroid tissues from E12.5-17.5 were subjected to immunofluorescent labeling of biomarkers (progenitors: NKX2-1; differentiation: thyroglobulin/TG); folliculogenesis: E-cadherin/CDH1; luminogenesis: mucin 1/MUC1; apical polarity: pericentrin/PCNT; basement membrane: laminin; growth: Ki67), quantitative RT-PCR analysis (Nkx2-1, Tg, Muc1) and transmission electron microscopy. Tg expression was detectable as early as E12.5 and gradually increased >1000-fold until E17.5. Muc1 and Nkx2-1 transcript levels increased in the same time interval. Prior to lobulation (E12.5-13.5), MUC1 and TG distinguished pre-follicular from progenitor cells in the developing isthmus characterized by intense cell proliferation. Luminogenesis comprised redistribution of MUC1+ vesicles or vacuoles, transiently associated with PCNT, to the apical cytoplasm and the subsequent formation of MUC1+ nascent lumens. Apical polarization of pre-follicular cells and lumen initiation involved submembraneous vesicular traffic, reorganization of adherens junctions and ciliogenesis. MUC1 did not co-localize with TG until a lumen with a MUC1+ apical membrane was established. MUC1 delineated the lumen of all newly formed follicles encountered in the developing lobes at E15.5-17.5. Folliculogenesis started before establishment of a complete follicular basal lamina. These observations indicate that embryonic thyroid differentiation is an asynchronous process consistent with the idea that progenitors attaining a stationary position in the connecting isthmus portion undergo apical polarization and generate follicles already at a primordial stage of thyroid development, i.e. foregoing growth of the lobes. Although the thyroid isthmus eventually comprises minute amounts of the total thyroid volume and contributes little to the overall hormone production, it is of principal interest that local cues related to the residence status of cells – independently of a prevailing high multiplication rate – govern the thyroid differentiation program.